Experimental and theoretical study of visible transitions in promethium-like tungsten. (28th April 2015) - Zhao, Z Z; Qiu, M L; Zhao, R F; Li, W X; Guo, X L; Xiao, J; Chen, C Y; Zou, Y; Hutton, R
Abstract: Visible transitions of promethium-like tungsten (W 13+ ) were studied using the Shanghai high temperature superconducting electron beam ion trap. The M1 transition between the ground state (4f 13 5s 2 2 F) fine structure levels was measured to be at 549.95 ± 0.06 nm. Seven other lines from W 13+ were also found and five of them were classified as belonging to transitions within the first excited configuration (4f 12 5s 2 5p). These lines were assigned with the help of relativistic configuration interaction calculations and collisional-radiative model predictions of the relative line intensities.